2019
DOI: 10.1039/c9ay00134d
|View full text |Cite
|
Sign up to set email alerts
|

Exploring asthenozoospermia seminal plasma amino acid disorder based on GC-SIM-MS combined with chemometrics methods

Abstract: Asthenozoospermia is a common cause of male infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…The other most predominant amino acids revealed in our study were alanine, glycine, aspartic acid, and serine. When these amino acids in seminal plasma were compared to those found in human seminal plasma (Li et al, 2019), profiles of some seminal plasma amino acids were similar to those profiles we found such as serine, glycine, and glutamic acids. The least abundant in our study, on the other hand, are tyrosine, methionine, alphaaminobutyric acid, allo-isoleucine, and asparagine, and are found to be similar with the low levels of amino acids of methionine and tyrosine in bull (Assumpção et al, 2005).…”
Section: Discussionsupporting
confidence: 72%
“…The other most predominant amino acids revealed in our study were alanine, glycine, aspartic acid, and serine. When these amino acids in seminal plasma were compared to those found in human seminal plasma (Li et al, 2019), profiles of some seminal plasma amino acids were similar to those profiles we found such as serine, glycine, and glutamic acids. The least abundant in our study, on the other hand, are tyrosine, methionine, alphaaminobutyric acid, allo-isoleucine, and asparagine, and are found to be similar with the low levels of amino acids of methionine and tyrosine in bull (Assumpção et al, 2005).…”
Section: Discussionsupporting
confidence: 72%
“…In all, the quantification of amino acids in human plasma by both GC-MS-and LC-MS-based mass spectroscopy was well established [23,24,28,31,32] and would ideally suit our validation study after improvement. As the key differences for LC-MS were often in terms of sample preparation and separation parameters, the comparison of those published LC-MS methods with the UHPLC-MS/MS method established by us could find that (a) our analysis was time-saving and economical and without any derivatization process; (b) a unique chromatographic configuration minimized ion suppression and yielded excellent analytic performance, especially for the isomers; and (c) this method could easily be extended to different sample matrices, such as plasma (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have published the quantitative analyses of amino acids in plasma [ 23 , 24 , 28 , 31 , 32 ], but these methods have never been applied in tissue homogenate. In this study, we developed a robust method for the quantitative analysis of underivatized amino acids in human tissue by UHPLC-MS/MS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effect of valine on motility was previously reported in a study about the composition of free amino acids in sperm of several fish species, where motility of perch semen was positively influenced by the presence of valine ( Lahnsteiner, 2010 ). Regarding human, the exploration on seminal plasma amino acid disorder in patients with asthenozoospermia revealed significantly lower values of this amino acid than in healthy controls, pointing out valine as a potential biomarker closely related to the clinical parameters of this pathology ( Li et al., 2019 ). The mechanism by which valine exerts a beneficial effect on sperm motility is still unclear ( Lahnsteiner, 2010 ; Li et al., 2019 ); however, it has been observed that there is a direct effect of dietary supplemented valine on the antioxidant enzymes superoxide dismutase and glutathione peroxidase of hypercholesterolemic rats ( Cojocaru et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%